INTEGRASI MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DAN STRATEGI MANAJERIAL UNTUK MENINGKATKAN LITERASI DIGITAL DAN HASIL BELAJAR BAHASA INDONESIA DI SEKOLAH DASAR - Tessar, Delia Oktaviana; Dzikri, Ilham Nur; Fatonah, Siti; Ratnasari, Dine Trio (LPPM UM Metro, 2025)
Advances in digital technology have had a significant impact on education, particularly on the Indonesian language learning process at the elementary school level. The use of technology in learning activities not only requires teachers to be able to use digital media effectively, but also requires the role of school management in creating a learning atmosphere that can adapt to the era of digital transformation. Based on this, this study aims to examine the relationship between the use of technology-based learning media and school managerial strategies to improve digital literacy and Indonesian language learning outcomes. This study applies a qualitative descriptive approach through a literature review sourced from various scientific publications, such as journals, books, and research reports published between 2019 and 2024. The results of the study revealed that the collaboration between the use of interactive digital media and the implementation of appropriate managerial strategies can increase student participation, creativity, and understanding in the Indonesian language learning process. Therefore, the integration of technological aspects and educational management is an important foundation in realizing innovative, collaborative learning, and focusing on improving students' digital literacy at the elementary school level.